واجب الطاعة الرئاسية في الوظيفة العمومية - سليمة روباش (جامعة محمد بوضياف المسيلة, 2018)
واجب الطاعة الرئاسية هو حجر الأساس في أداء المرفق العمومي لأعماله وبالتالي يحتل الصدارة والأولوية في واجبات الموظف العمومي كالتزام يقضي بامتثال وتنفيذ المرؤوس للأوامر الصادرة عن رؤسائه الإداريين، مع التزامه باللباقة والاحترام في التعامل معهم، كما أنه واجب يقوم على وجود رئيس ومرؤوس وأمر رئاسي هذا الأخير الذي يعتبر وسيلة التواصل بين طرفي الطاعة إضافة إلى أن واجب الطاعة الرئاسية تتحكم في مداه، عدة عوامل منها ما يتعلق بسياسة الحكم أو نوع النظام الإداري السائد، أو حتى طبيعة الوظيفة العامة في حد ذاتها. أضف إلى أنه يمكن القول أن واجب الطاعة الرئاسية العامل الرئيسي لاستمرار وحسن سير المرافق العامة، الأمر الذي ثار معه خلاف فقهي كبير حول امتداد نطاقه ليشمل الأوامر الرئاسية غير المشروعة، حماية لاستقرار وسيرورة المرافق على حساب مبدأ المشروعية، الأمر الذي اختلفت فيه النظريات الفقهية والتي لم يظهر أن المشرع الجزائر استقر على أي منها. أما بالنسبة لإخلال المرؤوس بواجب الطاعة فإن ذلك لا يؤدي إلى قيام المسؤولية التأديبية فقط، بل يمكن في ذات الوقت أن يؤدي إلى قيام المسؤولية المدنية والجنائية، كل ذلك في إطار تقديم ضمانات هامة للموظف القائم بواجب الطاعة، تعصمه من آثار المسؤولية التي تحيط به، شرط أن يكون ما بدر منه تنفيذا لأوامر رؤسائه الإداريين. The duty of obeying superiors at work is the cornerstone of the well performance of the public service. Therefore, it constitutes the top priority in the duties of the public servant as a commitment to follow and execute the orders of his superiors, while being committed to respect and courtesy in dealing with them. It is also a duty based on the existence of a superior, a public servant and superior orders. This latter serves as a means of communication between the two. In addition, many factors control the scope of the duty of obedience to superiors, including the policy of governance, the type of administrative system, or even the nature of the public service. Moreover, it can be said that the duty of superior obedience is the main factor in the efficient operation of services in public facilities, which has led to a great jurisprudential dispute over the extension of its scope to include illegal superior orders, to protect the stability and operation of facilities at the expense of the principle of legality. This caused the rise of different doctrinal views which did not show that the Algerian legislator has settled on any of them. As for the violation of the subordinate to the duty of obedience, this leads not only to disciplinary responsibility, but also to civil and criminal liability. In the context of providing important guarantees to the duty-bearer to protect him from the consequences of his responsibility provided that what is required of him in implementation of the orders of his superiors.
Keywords: • الطاعة الرئاسية • المرفق العمومي • الموظف العمومي • النظام الإداري السائد • مبدأ المشروعية • المسؤولية التأديبية • المسؤولية المدنية والجنائية